2020
DOI: 10.1155/2020/8209313
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Serum Angiopoietin-2 in Patients with Hemorrhage in Adult-Onset Moyamoya Disease

Abstract: Background. Moyamoya disease (MMD) is a progressive occlusive cerebrovascular disease that is characterized by abnormal angiogenesis at the base of the brain. This pathological abnormal angiogenesis is susceptible to disturbances, including spontaneous hemorrhage and vasogenic edema. However, the underlying mechanisms of pathological angiogenesis and occurrence of hemorrhage are unclear. Angiopoietins play a fundamental role in the pathophysiology of central nervous system disorders in angiogenesis. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous studies confirmed that the VEGF levels were nearly identical to those in healthy cohorts, confirming an active neovascularization state in patients with MMD ( 7 ) despite decreased serum caveolin-1 concentrations associated with negative arterial remodeling ( 18 ). Increased serum angiopoietin-2 levels have been described ( 19 ), and angiopoietins contained in these fluids may facilitate vascular responses that regulate angiogenesis via an autocrine release in patients with MMD ( 20 ). Additionally, surgical bypass can elevate VEGF-A 165 a/b ratios in MMD and intracranial atherosclerotic disease ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies confirmed that the VEGF levels were nearly identical to those in healthy cohorts, confirming an active neovascularization state in patients with MMD ( 7 ) despite decreased serum caveolin-1 concentrations associated with negative arterial remodeling ( 18 ). Increased serum angiopoietin-2 levels have been described ( 19 ), and angiopoietins contained in these fluids may facilitate vascular responses that regulate angiogenesis via an autocrine release in patients with MMD ( 20 ). Additionally, surgical bypass can elevate VEGF-A 165 a/b ratios in MMD and intracranial atherosclerotic disease ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angiopoietin-1 (Ang-1) and angiopoietin-2 (Ang-2) levels in serum were higher in patients with MMD than in healthy controls. 44,60 Blecharz et al 14 Demonstrated that Ang-2, but not Ang-1, was significantly overexpressed in the intracranial artery of patients with MMD. Ang-2 mediated MMD cerebrovascular disintegration by weakening the EC barrier in an autocrine manner, and the destabilization of brain ECs could be partially restored by the inhibition of Ang-2 by exogenous administration of Ang-1.…”
Section: Hepatocyte Growth Factormentioning
confidence: 99%
“…The results obtained by the group may identify cerebral endothelial cells as a potential source of vessel-destabilizing factors, inducing plastic and unstable neovascularization and cerebrovascular disintegration in MA, mediated by the autocrine release of the pro-angiogenic cytokine ANG2, thereby elucidating a mechanism that may contribute to cerebrovascular hemorrhagic and ischemic events in MA. 190 Yu et al 191 showed that ANG2 may be involved in the pathophysiology of increased angiogenesis in adult hemorrhagic MA and may also be a prognostic factor of intracranial hemorrhage in adult MA patients. Infection is linked to Tie2 signaling disruption that is related to vascular leakage.…”
Section: Molecular Biomarkers Of Moyamoya Angiopathymentioning
confidence: 99%